I am having troubles understanding how to operate with generating functions to obtain a final formula. I have been looking to the answer to this question: Exponential generating function and number of balls .

$$\color{red}{\left(\frac{x^2}{2!}+\frac{x^4}{4!}\right)}\color{green}{\frac12\left(e^x+e^{-x}\right)}\color{blue}{e^x}.$$ This expands to $$\frac12\cdot\frac{x^2}{2!} + \frac12\cdot\frac{x^4}{4!} + \sum_{n=2}^\infty \frac1{16}2^nn(n-1)\frac{x^n}{n!} + \sum_{n=4}^\infty\frac1{768}2^nn(n-1)(n-2)(n-3)\frac{x^n}{n!}. $$ Simplification yields $$\frac{x^2}{2!}+3\frac{x^3}{3!}+13\frac{x^4}{4!} + \sum_{n=5}^\infty \frac1{768} 2^nn(n-1)(n^2-5n+54)\frac{x^n}{n!}. $$

What are the steps to obtain this and the simplification? I can't see how to get from one to another I have tried a different approach, since $$ e^x + e^{-x} = \sum_{n=0}^\infty {2x^{2n}\over (2n)!}; \; e^x = \sum_{n=0}^\infty {x^{n}\over n!}, $$ Multiplying everything, I obtain: $$ \frac{1}{2}\frac{x^2}{2!}\left(\sum_{n=0}^\infty\frac{2x^{2n}}{(2n)!}\right)\cdot \left(\sum_{n=0}^\infty \frac{x^n}{n!}\right) + \frac{1}{2}\frac{x^4}{4!}\left(\sum_{n=0}^\infty\frac{2x^{2n}}{(2n)!}\right)\cdot \left(\sum_{n=0}^\infty \frac{x^n}{n!}\right) $$

Removing the 2 of the numerator of the fractions and simplifying $x^{2n}/2n!$ for $x^{n}/n!$; and if I understand multiplication correctly, I should have: $$ \sum_{k=0}^{n}\binom{n}{k}\frac{x^n}{n!} $$ as a result of both the multiplications, but doesn't look like any form of the right answer.

PS: Decided to make another question instead of commenting the answer because it is 2 years old already.

  • 1
    $\begingroup$ You do know that $(e^x+e^{-x})e^x=e^{2x}+1$, don't you? $\endgroup$ – Lord Shark the Unknown Dec 8 '17 at 21:25
  • $\begingroup$ Yeah, I know that, did not see that simple thing, that's embarrasing. But I still don't know how to get to the second step from:$$ \frac{1}{2}\frac{x^2}{2!}+ \frac{1}{2}\frac{x^4}{4!} + \frac{1}{2}\frac{x^2}{2!}\cdot\sum_{n=0}^{\infty}\frac{(2x)^n}{n!} + \frac{1}{2}\frac{x^4}{4!}\cdot \sum_{n=0}^{\infty}\frac{(2x)^n}{n!}; $$ To start the sum from n=2 and n=4 I understand it is needed to multiply by $n(n-1)$ and $n(n-1)(n-2)(n-3)$ but I don't know where the $1/16$ and $1/768$ come from. $\endgroup$ – Geid Dec 8 '17 at 21:57

The term with $\frac{1}{16}$ arises as follows: \begin{align*} \frac{x^2}{2}\cdot\frac{1}{2}e^{2x} &= \frac{1}{4}x^2\sum_{n=0}^\infty \frac{2^nx^n}{n!} \\ &= \frac{1}{4}\sum_{n=0}^\infty \frac{2^nx^{n+2}}{n!} \\ &= \frac{1}{16}\sum_{n=0}^\infty \frac{2^{n+2}x^{n+2}}{n!} \\ &= \frac{1}{16}\sum_{n=2}^\infty \frac{2^nx^n}{(n-2)!} \\ &= \frac{1}{16}\sum_{n=2}^\infty n(n-1)\frac{2^nx^n}{n!}. \end{align*} The other term arises similarly, starting from $\frac{x^4}{24}\cdot\frac{1}{2}e^{2x}$.

  • $\begingroup$ OK, I see it now, thanks a lot. I didn't know how to operate with the terms of the sum, but now it's clear. $\endgroup$ – Geid Dec 8 '17 at 22:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.